FSESP Foundation - Public Health Service - in Algoas (1960-1990): the knowledge and the actions of midwives and curious women in the light of Collière (2022)
Carried out by the Fundación Servicio Especial en Salud Pública(FSESP) in Algoas between 1960 and 1990, this is a sociohistoricalstudy that describes the work of recruiting, training and supervising midwives and curious women. Both written and oral sources were used, produced in interviews from oral thematic history. The participants were two health visitors, six midwives, three curious women, a doctor, and a nurse. The results showed that the midwives and curious womenwere recruited and trained by the health visitors. When they could assist a birth, they received a bag with materials and were accompanied by the health visitors or nurses to clean the bags and renew the instructions. The actions of the midwives/curious women were analyzed from the referential theory of Marie Françoise Collière, which revealed that they provided care to patients based on knowledge and practices acquired through experience, seeking to secure the continuity of life. It was concluded that the FSESP was an important healthservice in Alagoas due to its activities in health education,revision, care and treatment of women in labor and newborns. Additionally, practices that have been improved throughout the years were found.